Kearifan Lokal Kota Batu Pada Karya Seni Batik Tulis Menggunakan Kajian Etnosains - Arinta Rezty Wijayaningputri; Belinda Dewi Regina (Journal on Education, 2023)
Written batik artwork is a cultural heritage that has high value and reflects the local wisdom of an area. Batu City, as one of the cities in Indonesia which is rich in cultural diversity and tradition, has local wisdom which is reflected in its written batik artwork. This study aims to analyze the local wisdom of Batu City in written batik artwork, using an ethnoscience study approach.The research method used is this approach using qualitative descriptive research. The subject of this study was an Ethnoscience Study based on Local Wisdom on Written Batik Art in Anjani Batik. The results of the study show that written batik artworks in Batu City contain various local wisdom values. The process of making written batik involves traditional knowledge passed down from generation to generation, such as selecting motifs, using natural colors, and fabric processing techniques.Ethnoscientific studies provide a deeper understanding of the local wisdom of Batu City in written batik artwork. This research can be the basis for appreciating and preserving the cultural heritage of Batu City and encouraging the development of a sustainable written batik industry. In addition, this research can also provide insight for artists, craftsmen, and art observers in exploring local wisdom values ​​in written batik artworks in other areas.